A robust super-tough biodegradable elastomer engineered by supramolecular ionic interactions. (April 2016) - Daemi, Hamed; Rajabi-Zeleti, Sareh; Sardon, Haritz; Barikani, Mehdi; Khademhosseini, Ali; Baharvand, Hossein
Abstract: Alginate-based supramolecular ionic polyurethanes (ASPUs) as mechanically tunable biomaterials with high strength and toughness in both dry and hydrated states are developed under metal-free conditions. The Young's modulus and tensile strength of ASPUs are tuned from 30 to 100 MPa, and 20 to 50 MPa, respectively. Interestingly, the ASPUs exhibit a small hysteresis loop, minimal loss of tensile strength and minimal creep deformation after 100 repetitive cycles which makes them of use for engineering of load-bearing tissues. This is the first report that describes a linear PU can resist a large number of cyclic stresses without significant stretching. These bio-based elastomers engineered by ionic interactions are biocompatible and biodegradable. The ASPUs demonstrate a similar in vivo degradation rate compared to polycaprolactone (PCL). These biomaterials also demonstrate a rapid self-healing and recovery after rupture, and have a linear biodegradation profile. Furthermore, histological examination of subcutaneous transplanted ASPUs after five months reveals low immunological response and low fibrosis.